Newer Perspectives in Lactate Threshold Estimation for Endurance Sports - A Mini-Review - Krishnan, A.; Guru, C. S.; Sivaraman, A.; Alwar, T.; Sharma, D.; Angrish, P. (Central European Journal of Sport Sciences and Medicine, 2021)
Lactate threshold (LT) estimation in endurance sports continues to be a widely controversial field amongst sports scientists and students despite beyond 50 years of research. With the advent of technology and superior sensors, LT research has ventured into newer fields involving wearables and artificial intelligence. Still, there is a felt need to understand the focused areas of LT research and to guide the students, sports scientists and coaches. The main aim of this mini-review is to identify research categories in a descriptive manner and to synthesize broad themes for future research from latest literature. A comprehensive electronic search in three databases was performed including only original free full text research articles conducted in athletes and heathy subjects, published in English between 2016 and 2020 following PRISMA guidelines. Out of screened 466 articles, 14 articles were finally shortlisted as per inclusion criteria and the findings were summarized. Five research categories were identified and reviewed. To conclude, there is a need for consensus in Graded Exercise test protocols used, LT concepts validity for specific sports and the application of valid, reliable noninvasive LT estimation methods in endurance sports. Synthesized broad themes would help guide sports scientists, students and researchers for future research.